The Addition of SNAGS is Faster to Reduce Pain and Disability Comparing with Conventional Therapy Only among HNP Lumbar Grade I and II - Asrul Sani; Susy Purnawati; Sugijanto Sugijanto; DPG Purwa Samatra; IPG Adiatmika; IG Ayu Widianti (Health Notions, 2022)
Herniated nucleus pulposus is a rupture of the annulus fibrosus intervertebral disc which can compression the excitatory tissue of the lumbar that comes out of the intervertebral foramen, causing radicular pain, and ultimately causing lumbar disability. This study aims to prove that the addition of SNAGS to conventional therapy is faster in reducing pain and disability in grade I and II lumbar HNP. This research was a experimental study with a control times series design which was carried out at dr. La Palaloi Hospital, Bhayangkara Hospital and Inggit Medical Clinic Makassar. The population was 50 samples with each group was consists of 20 people according to pocock formula and each group had given 2 times exercises a week for 6 weeks, simple random sampling using consecutive sampling method with lottery technique. The primary outcomes measured were pain and disability used VAS and ODI that were performed every week. Data analysis using Kruskall-Wallis and Wilcoxon showed the change in the mean VAS before the intervention was 5.84±1.17 and the mean VAS after the third week of intervention was 4.90±1.04 with p-value = 0.000 and a change in the mean The ODI before the intervention was 40.60±9.21 and the mean ODI after the fourth week of intervention was 32.90±6.79 with p-value = 0.0000. While the treatment group showed a change in the mean VAS before the intervention was 5.68±1.00 and the mean VAS after the second week of intervention was 4.57±0.79 with p-value = 0.000 and change in the mean ODI before intervention was 40.50±8.43 and the mean ODI after the third week of intervention was 28.60±6.23 with p-value = 0.000 which means that the control group was effective for changes in pain in the third week and effective for changes in disability in the fourth week, while the study group was effective for changes in pain in the second week and effective for changes in disability in the third week. There was a significant difference in pain changes in the control group and the treatment group in the second week with p-value = 0.014 and a significant difference in the change in disability in the control group and the treatment group in the third week with p-value = 0.011. It was concluded that the addition of SNAGS to conventional therapy was faster in reducing pain in the second week and disability in the third week in cases of grade I and II lumbar HNP. Keywords: pain; disability; HNP lumbar grade I and II; conventional therapy; SNAGS